Cellular reactivity to the p. Falciparum protein trap in adult kenyans: novel epitopes, complex cytokine patterns, and the impact of natural antigenic variation. - Flanagan, K; Plebanski, M; Odhiambo, K; Sheu, E; Mwangi, T; Gelder, C; Hart, K; Kortok, M; Lowe, B; Robson, K; Marsh, K; Hill, A (2006)
Malaria vaccines based on thrombospondin-related adhesive protein of Plasmodium falciparum (Pf TRAP) are currently undergoing clinical trials in humans. This study was designed to investigate naturally acquired cellular immunity to Pf TRAP in adults from a target population for future trials of TRAP-based vaccines in Kilifi, Kenya. We first tested reactivity to a panel of 53 peptides spanning Pf TRAP and identified 26 novel T-cell epitopes. A panel of naturally occurring polymorphic variant epitope peptides were made to the most commonly recognized epitope regions and tested for ability to elicit IFN-gamma, IL-4, and IL-10 production. These data provide for the first time a complex cytokine matrix mapping naturally induced T-cell responses to TRAP and suggest that T-cell responses boosted by vaccination with Pf TRAP could stimulate the release of competing pro- and anti-inflammatory cytokines. They further define polymorphic variants able to boost specific Th1, Th2, and possibly Tr1 reactivity.